Self-Rectified Graphite-Based Reprogrammable One-Time Programmable (RS-OTP) Memory for Embedded Applications - Chen, Ying-Chen (Frontiers in Nanotechnology, 2021)
A graphite-based RRAM device with a self-rectifying characteristic named “non-linearity (NL)” is developed for a high-density crossbar array for in-memory computing with low power and high scalability. Meanwhile, the reprogrammable functions are presented in self-selected RRAM as a promising candidate for one-time programmable (OTP) in the emerging memory-embedded applications such as security, system-on-chip (SoC), and Internet of Things (IoT).